O ensino de história em escolas públicas do interior de Pernambuco: currículo, saberes e práticas - Bezerra, Ricardo José Lima (2014)
The theme of this work is the relationship between prescribed curriculum, curriculum knowledge and experiential teaching and educational practices of teaching history in public high schools at interior of Pernambuco. We start from the premise that educational practice in history is much more driven conceptions of history and experience-based knowledge derived from education teachers than by curricular and pedagogical orientations arising from institutional and official documents. We base our work on the concepts and theories formulated by authors such as Maurice Tardif et al (2001, 2005 and 2010), Ivor Goodson (1995), Moreira and Silva (2011), Gimeno Sacristan (1998), Francisco Imbernon (2010), Antoni Zabala (1998 ) among others, on teacher knowledge and curriculum and Silva and Fonseca (2007) theories, Davies (1996); Siman (2004), Monteiro (2007) Bittencourt (2009), Gasparello (2001, 2007), Martin (2007) among others, to study the teaching of history, in addition to the documents that constitute the curriculum policy in history and Pernambuco in Brazil, such as the National Curricular Parameters for the Humanities and its technologies, Theoretical and Methodological Guidelines for teaching History from the Department of Education of Pernambuco, beyond the political-pedagogical projects and Teachers of Schools Planning Teacher Ivonita Alves Guerra and the School for Excellence in Secondary Education Arnaldo Assunção empiricus locus of this work. We seek to conduct this research through a qualitative approach, through the use of recorded oral interviews, semi-structured questionnaires and structured observations. Research has shown us that history teachers recognize the importance of official curriculum documents for the teaching of this subject, however pursue their educational practice based more on their teaching experiences acquired over time than in the curricular requirements for teaching history in stage of basic education